Development of Croatian Terminology in Wood Technology - Vlatka Jirouš-Rajković (University of Zagreb, Faculty of Forestry and Wood Technology, 2017)
Experts from Wood Technology Division at the University of Zagreb, Faculty of Forestry have started work on the project “Development of Croatian Terminology in Wood Technology”, which has been accepted for the call “Development of Croatian Special Field Terminology (STRUNA)” published by Croatian Science Foundation in April 2016. The project is approved for support from October 1, 2016 to September 30, 2017. The two main goals of the project are to build a Croatian terminology in woodworking profession and to promote its popularization. The main task of the project DRVNA is to create a database with assembled woodworking terms, their definitions and equivalents in English and German. The terms stored in the electronic database STRUNA will be further classified as recommended, admitted, deprecated, obsolete, colloquial and proposed terms. The project has a team of 29 professors, associate professors, assistant professors and assistants from the Wood Technology Department of Faculty of Forestry, University of Zagreb, together with colleagues from the Institute of Croatian Language and Linguistics, who provide the linguistic and terminographic verifcation of the terminological work in progress.